WhatsApp Groups as a Place for Breastfeeding and MP-ASI Education in the Covid-19 Pandemic Era - Adinda Putri Sari Dewi; Eka Novyriana; Eti Sulastri (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Based on the data from the Kebumen District Health Office, shows that the Sempor I Public Health Center has a corrected exclusive breastfeeding coverage of 10 the lowest compared to other health centers in 2019. Meanwhile, Bajiruyung Village is one of the villages in the Sempor I Health Center area whose exclusive breastfeeding coverage is below 50%. . This is because there is still a lack of understanding of the community and even health workers about the benefits and importance of exclusive breastfeeding for infants aged 0-6 months and the technique of giving complementary feeding so that many babies aged 4 months have been given MP-ASI and there is no breastfeeding support group. The purpose of this community service is the formation of a WhatsApp Group as a place for breastfeeding and complementary feeding education in the Covid-19 Pandemic Era. Community service methods include online training on breastfeeding and complementary feeding, local menu MP-ASI competitions online, and evaluation. The results of community service are 20 people who are willing to join the WhatsApp ASI and MP-ASI WhatsApp groups. Results The level of knowledge before being given counseling about breastfeeding showed an average score of 65 and after training 78 from the range of values 0-100 or an increase of 10 points. The level of knowledge before being given counseling about MP-ASI increased by 9 points. While the results of the assessment of the local MP-ASI menu were 6 people who got good scores, 10 people got enough marks and 4 others got fewer marks. The conclusion after the community service was the formation of the breastfeeding and complementary feeding WhatsApp group and increasing knowledge of mothers about breastfeeding and complementary feeding.